Design and Simulation of Multichannel Dynamic Measurement Control System. (30th September 2022) - Shen, Dawei; Pei, Dongxing; Ma, Tiehua
Abstract : The circuit system designed in this paper uses FPGA and single-chip microcomputer as the main chips. It uses VHDL language programming and performs functional simulation and verification of the core control program through ModelSim software, and finally, a storage-type dynamic measurement and control system with one-to-multiple channels, adjustable trigger modes, and optional sampling frequency is realized. At the same time, the system is further optimized in terms of power consumption and volume. The storage measurement and control system can successfully record eight-channel dynamic voltage signals, and the relative error of the experimental results is less than 2% through the simulation trigger experiment and Hopkinson bar experiment loading.